Socio-Economic Impacts of Mobile Penetration in SAARC Countries with Special Emphasis on Bangladesh - Chowdhury, Muktasha Deena (Asian Business Review, 2015)
Throughout the last decade, the world has observed a surprising growth of mobile subscribers over the South Asian region. This has brought significant changes in the socio-economic environment of the SAARC (South Asian Association for Regional Cooperation) countries as well as in Bangladesh. The growth of mobile telecom industry has not only helped in developing a vital infrastructure of the country but also has played an important role in shaping social behavior. At present, a mobile phone is not just a tool for basic conversation; it is also a service device for all types of services like health, education, agriculture, mobile money for unbanked banking, commerce and businesses, citizen services, disaster responses or even an FM radio that we found in this study. It is changing the socio- economic condition and overall lifestyle of millions by creating employment opportunities and uplifting the living standard. This study aims to study the socio-economic changes in SAARC countries as well as in Bangladesh caused due to mobile penetration with a view to utilizing the outcomes, for our advancement. This study is quantitative in nature. Data collected from both primary and secondary data sources. Primary data collected from 100 individuals, 50 from urban and 50 from rural, using convenience sampling technique with a set of questionnaires designed for this study. Secondary data is obtained from secondary data sources, ITU (International Telecommunication Union), BTRC (Bangladesh Telecommunication Regulatory Commission), BBS (Bangladesh Bureau of Statistics), UNDP( United Nations Development Program),  etc will be used for the research. After collecting the data, they were transcribed, tabulated and analyzed in terms of the research objectives.
Keywords: Socio-Economic Impact; Mobile Penetration; GNI; GDP; Education Index